Perceptions of Oral Health-Related Care for Children with Autism Spectrum Disorder: A Scoping Review - AlBhaisi, Ismail Nabil; Mohd-Said, Shahida; Lim, Yan Jia; Mohd-Dom, Tuti Ningseh; Zakaria, Ahmad Shuhud Irfani; McGrath, Colman Patrick (Journal of Dentistry Indonesia, 2024)
Objective: This review aimed to seek insights into the challenges faced by caregivers and children with autism spectrum disorder (ASD) when performing and accessing oral care and their recommendations to overcome the matter. Methods: Six electronic databases were used to search for published English full articles using a standardised strategy and grouped using thematic analysis as findings to the study’s goal. Results: The initial screening found 46 relevant articles, but 21 were deemed eligible. Studies were mostly observational (18 crosssectional surveys and 3 case-controls), retrieving data from online or face-to-face surveys and insurance health info. The perceptions and potential solutions made by parents, teachers, doctors, and individuals with ASD were diverse but mostly consistent in most studies with a focus on issues of oral health as low priority, incompetency in oral health care performance at home, children’s cooperation and involuntary behaviours in dental settings, and constraints in related resources. Conclusion: Carers’ lack of awareness and prioritisation of treatment for children with ASD, challenges in performing oral care at home, concerns over oral health care provided by caregivers in educational institutions and dental clinics, and challenges in accessing more supportive oral health care services were highlighted as barriers to oral care.